Smartphone-Based Hearing Screening at Primary Health Care Clinics. Issue 2 (March 2017) - Louw, Christine; Swanepoel, De Wet; Eikelboom, Robert H.; Myburgh, Hermanus C.
Abstract : Objective: To evaluate the performance of smartphone-based hearing screening with the hearScreen ™ application in terms of sensitivity, specificity, referral rates, and time efficiency at two primary health care clinics. Design: Nonprobability purposive sampling was used at both clinics. A total of 1236 participants (mean age: 37.8 ± SD 17.9 and range 3 to 97 years; 71.3% female) were included in the final analysis. Participants were screened using the hearScreen ™ application following a two-step screening protocol and diagnostic pure-tone audiometry to confirm hearing status. Results: Sensitivity and specificity for smartphone screening was 81.7 and 83.1%, respectively, with a positive and negative predictive value of 87.6 and 75.6%, respectively. Sex [ χ 2 (1, N = 126) = 0.304, p > 0.05] and race [ χ 2 (1, N = 126) = 0.169, p > 0.05)] had no significant effect on screening outcome for children while for adults age ( p < 0.01; β = 0.04) and sex ( p = 0.02; β = −0.53) had a significant effect on screening outcomes with males more likely to fail. Overall referral rate across clinics was 17.5%. Initial screening test times were less than a minute (48.8 seconds ± 20.8 SD) for adults and slightly more than a minute for children (73.9 seconds ± 44.5 SD). Conclusions: The hearScreen ™ smartphone application provides time-efficient identification of hearing loss with adequate sensitivity and specificity for accurate testing at primary health care settings.